PDF-embedded multimedia content in medical publishing and JPNIM’s next goals - Fanos, Eleonora (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2014)
The aim of this contribution is to understand how multimedia content (including 3D illustrations, audios and videos) can be effectively inserted in online medical publications and to review the current panorama in medical publishing. The overall analysis focuses on the PDF versions of articles; the online (html) versions in the publisher’s website will be analyzed only when needed for comparison purposes. The reader will also be presented with the goals that the Journal of Pediatric and Neonatal Individualized Medicine (JPNIM) has for the near future regarding multimedia contents. JPNIM has been conceived from its origins to be in the form of downloadable comprehensive PDFs so as to facilitate their fruition and storage; from the very beginning, we decided to avoid the creation of supplemental material files and include all relevant images and tables inside the article. In these years, we have continued to search for better and more engaging means of medical communication, introducing for example Question and Answer, Interview, and Mini Atlas series of articles. Our striving for innovation is still ongoing: from now on, we also intend to accept 3D illustrations, audios and videos (e.g., with slide presentations or demonstrations of clinical procedures) to integrate (as PDF-embedded multimedia) into each kind of article, and we are planning to start a new Video series, featuring the explanation of medical procedures. You are welcome to send your contributions for evaluation.